Antifungal Effect of Teucrium polium and Zingiber officinale Extracts on Clinical isolates of Candida Species - N Shoaie; P Mohammadi; SH Roudbar Mohammadi (Armaghane Danesh Bimonthly Journal, 2012)
Abstract: